The Creolization of Political Theory and the Dialectic of Emancipatory Thought: A Plea for Synthesis - Michael Neocosmos (Journal of French and Francophone Philosophy, 2017)
The paper discusses Jane-Anna Gordon's important idea of the Creolization of Poitical Theory with reference to the work of Jean-Jacques Rousseau and Frantz Fanon. It makes an argument for synthesizing this initiative with dialectical thought in order to transcend the analytical vision which gave birth to the creolizing of theory.  This synthesis is proposed in order to make sense of the real of any politics of universal emancipation and to incorporate the theoretical inventions of popular actions.